The masculine logic of DDR and SSR in the Rwanda Defence Force. (August 2019) - Duriesmith, David; Holmes, Georgina
Since the 1994 genocide and civil war, the Rwandan government has implemented an externally funded disarmament, demobilization and reintegration/security sector reform (DDR/SSR) programme culminating in the consolidation of armed groups into a new, professionalized Rwanda Defence Force. Feminists argue that DDR/SSR initiatives that exclude combatant women and girls or ignore gendered security needs fail to transform the political conditions that led to conflict. Less attention has been paid to how gendered relations of power play out through gender-sensitive DDR and SSR initiatives that seek to integrate women and transform hyper-masculine militarized masculinities. This article investigates how Rwanda's DDR/SSR programme is governed by an oppressive masculine logic. Drawing on critical studies on men and masculinities and feminist work on peacebuilding, myths and the politics of belonging, it argues that Rwanda's locally owned DDR/SSR programme places the military and militarization at the centre of the country's nation-building programme. Through various 'boundary-construction' practices, the Rwandan government attempts to stabilize the post-1994 gender order and entrench the hegemony of a new militarized masculinity in Rwandan society. The case study draws on field research conducted in 2014 and 2015 and a discourse analysis of historical accounts, policy documents and training materials of the Rwanda Defence Force.